Characterization of Tribological Behaviour of Surface Topographies by Roughness Measurement at the Beginning of the Wear Process - Barányi, István (Acta Technica Jaurinensis, 2020)
The examination of the tribological processes can be implement by different methods. In the initial stage of the abrasive wear process, the microtopography of steels drastically changes until it reaches a stable state. This change can be described by different methods. One of the methods is the characterisation with the help of roughness parameters. In this paper validated simulation algorithm has been used to predict the modification of the roughness parameters. Manufactured microtopographies with same arithmetical mean height (Sa) value can be modelled to the destroying with the help of abrasive worn microtopography. It was found the main roughness parameters named Sa, Sq, Ssk, Sku modification strongly depending to the manufacturing technology.